The first complete chloroplast genome of Liparis nervosa and its phylogenetic position within Orchidaceae - Wang, Xujun (Mitochondrial DNA B Resour, 2019)
Liparis nervosa is a plant of the family Orchidaceae and mainly distributed in subtropical and tropical regions of the world. In Chinese traditional medicine, it has been used for the treatment of hemostasis, carbuncle, and furuncle for centuries. The chloroplast (cp) genome of L. nervosa, sequenced based on next-generation platform (NEOSAT), is 157,274 bp in size. The cp genome encodes 130 genes, including eight rRNA genes, 85 protein-coding genes (PCGs), and 37 tRNA genes. Phylogenetic relationship analysis based on complete cp genome sequences exhibited that both of L. nervosa and L. loeselii were phylogenetically closer to Dendrobium officinale.